Development Of Qana’ah Instrument Using Confirmatory Factor Analysis - Saifuddin, Ahmad; Putri, Lintang Seira; Sari, Hellenna Kartika (Academic Journal of Psychology and Counseling, 2023)
Some people experience adversities that affect their psychological conditions, e.g., stress, depression, less happiness, and less psychologically prosperous. One solution to these psychological problems is to increase the attitude of qana’ah/contentment (accepting and being satisfied with what they have). This situation calls for a good qana’ah instrument to provide necessary interventions. This study aimed to test the validity and reliability of the qana’ah instrument. Researchers gathered 670 participants across all Indonesian provinces using the area random sampling approach. The results of the content validity test using Aiken’s formula show that each item in the instrument has a validity coefficient between 0.79 – 0.92. The estimated reliability coefficient of Alpha Cronbach is 0.992. The research also found that the item discrimination index ranged from 0.586 to 0.979, while loading factor of the items ranged from 0.463 to 0.875. The instrument also showed goodness-of-fit based on the Confirmatory Factor Analysis (CFI=0.987 (>0.900); GFI=0.925 (>0.900); AGFI=0.914 (>0.900); NFI=0.942 (>0.900); and RMSEA=0.0197 (<0.08)). The results of this study indicate that the measuring instrument is valid and reliable.